Ferrite sintered magnet and manufacturing method of ferrite sintered magnet
Patent Information
- Application Number
- JP2023139958
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0017】 本開示の実施形態によれば、従来のCaLaCo磁石を上回る高い残留磁束密度Br及び高い保磁力HcJを有するフェライト焼結磁石、または、従来のCaLaCo磁石と同等以上の高い残留磁束密度Br及び高い保磁力HcJを有するとともに、従来のCaLaCo磁石よりもCo使用量を削減することができるフェライト焼結磁石の提供が可能となる。
Smart Images

Figure 2025033920000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered ferrite magnet and a method for producing a sintered ferrite magnet. [Background technology]
[0002] Although the maximum energy product of ferrite sintered magnets is only about one-tenth that of rare earth sintered magnets (e.g., NdFeB sintered magnets), they offer excellent cost performance because their main raw material is inexpensive iron oxide, and they are characterized by being extremely chemically stable.As a result, they are used for a variety of purposes, including various motors and speakers, and even today they are the largest magnet material in terms of global production volume.
[0003] A typical sintered ferrite magnet is a Sr ferrite with a magnetoplumbite structure, and its basic composition is SrFe 12 O 19 In the late 1990s, SrFe 12 O 19 Sr 2+ Part of La 3+ Replaced with Fe 3+ Part of Co 2+ The magnetic properties of ferrite magnets were greatly improved with the commercialization of Sr-La-Co sintered ferrite magnets (hereinafter sometimes abbreviated as "SrLaCo magnets"), which replaced the ferrite with Sr-La-Co. In 2007, Ca-La-Co sintered ferrite magnets (hereinafter sometimes abbreviated as "CaLaCo magnets"), which have even better magnetic properties, were also commercialized.
[0004] Co is essential for the SrLaCo magnets described in Patent Documents 1 and 2 and the CaLaCo magnets described in Patent Document 3 to obtain high magnetic properties. SrLaCo magnets contain Co at an atomic ratio of about 0.2 (Co / Fe=0.017, i.e., about 1.7% of the Fe content), while CaLaCo magnets contain Co at an atomic ratio of about 0.3 (Co / Fe=0.03, i.e., about 3% of the Fe content). The price of Co (Co oxide) is ten to several tens of times that of iron oxide, the main raw material of ferrite sintered magnets. Therefore, the CaLaCo magnets inevitably have higher raw material costs than the SrLaCo magnets. The greatest feature of ferrite sintered magnets is their low cost, so even if they have high magnetic properties, they are difficult to accept in the market if they are expensive. Therefore, there is still a high demand for SrLaCo magnets worldwide.
[0005] Meanwhile, among the various applications in which sintered ferrite magnets are used, such as motors and speakers, there is a strong demand for higher performance in motors for automotive electrical equipment, motors for home appliances, etc. In recent years, against the backdrop of rising prices of rare earth raw materials and the emergence of procurement risks, the application of sintered ferrite magnets to industrial motors and drive motors and generators for EVs (Electric Vehicles) / HEVs, where only rare earth magnets were used until now, is being considered.
[0006] For these applications, a high residual magnetic flux density B is required to suppress demagnetization due to a strong demagnetizing field when the magnet is thinned and at high temperatures (e.g. 140°C). r and high coercive force H cJ There is a demand for a sintered ferrite magnet having the above properties. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-149910 [Patent Document 2] Japanese Patent Application Publication No. 11-154604 [Patent Document 3] JP 2006-104050 A Summary of the Invention [Problem to be solved by the invention]
[0008] The embodiments of the present disclosure have a high residual magnetic flux density B over conventional CaLaCo magnets. r and high coercive force H cJ A ferrite sintered magnet with a high residual magnetic flux density B equivalent to or higher than that of conventional CaLaCo magnets. r and high coercive force H cJ This makes it possible to provide a sintered ferrite magnet that has the above properties and that can reduce the amount of Co used compared to conventional CaLaCo magnets. [Means for solving the problem]
[0009] A non-limiting exemplary sintered ferrite magnet of the present disclosure is represented by the general formula: Ca, R, Fe, and Co, which shows the atomic ratio of the metal elements (wherein R is at least one rare earth element and essentially contains La): x R 1-x Fe 2n-y Co y In the formula, x, y, and n (wherein 2n is a molar ratio expressed as 2n=(Fe+Co) / (Ca+R)) are 0.5 <x≦0.65、 0.2 <y<0.35、 6.5≦2n-y<11.0, and contains 1.0 mass% or less (excluding 0 mass%) of Si calculated as SiO2.
[0010] In one embodiment, the material contains 0.55 mass % or more and 0.75 mass % or less of Si calculated as SiO 2 .
[0011] In one embodiment, 0.27≦y≦0.32.
[0012] A non-limiting exemplary method for producing a sintered ferrite magnet according to the present disclosure is a method for producing a sintered ferrite magnet according to the general formula: Ca, R, Fe, and Co, which shows the atomic ratio of the metal elements (wherein R is at least one rare earth element and essentially contains La). x R 1-x Fe 2n-y Co y In the formula, x, y, and n (wherein 2n is a molar ratio expressed as 2n=(Fe+Co) / (Ca+R)) are 0.5 <x≦0.65、 0.2 <y<0.35、 6.5≦2n-y<11.0, A raw material powder mixing process for mixing raw material powders satisfying the above to obtain a mixed raw material powder; a calcination step of calcining the mixed raw material powder to obtain a calcined body; A grinding step of grinding the calcined body to obtain a powder of the calcined body; A molding step of molding the powder of the calcined body to obtain a molded body; a sintering step of sintering the molded body to obtain a sintered body; Including, After the calcination step and before the molding step, 1.0 mass% or less (excluding 0 mass%) of SiO2 is added to 100 mass% of the calcined body or powder of the calcined body.
[0013] In one embodiment, after the calcination step and before the molding step, 0.55 mass% or more and 0.75 mass% or less of SiO2 is added to 100 mass% of the calcined body or powder of the calcined body.
[0014] In one embodiment, 0.27≦y≦0.32.
[0015] In one embodiment, in the firing step, the average heating rate in the temperature range from room temperature to 1100° C. is less than 13.3° C. / min, and the average heating rate in the temperature range from 1100° C. to the firing temperature is 1° C. / min or more and 10° C. / min or less.
[0016] In one embodiment, after the calcination step, no CaCO3 is added before the molding step. [Effect of the Invention]
[0017] According to an embodiment of the present disclosure, a ferrite sintered magnet having a higher residual magnetic flux density B than that of a conventional CaLaCo magnet r and a higher coercive force H cJ can be provided, or a ferrite sintered magnet having a residual magnetic flux density B equal to or higher than that of a conventional CaLaCo magnet r and a higher coercive force H cJ and capable of reducing the Co usage amount compared to a conventional CaLaCo magnet. [Embodiment for Carrying Out the Invention]
[0018] 1. Ferrite Sintered Magnet The ferrite sintered magnet of the present disclosure has a general formula showing the atomic ratio of metal elements of Ca, R, Fe, and Co (where R is at least one rare earth element and an element essentially containing La): Ca x R 1-x Fe 2n-y Co y wherein x, y, and n (where 2n is a molar ratio and is represented by 2n = (Fe + Co) / (Ca + R)) satisfy 0.5 < x ≤ 0.65, 0.2 < y < 0.35, 6.5 ≤ 2n - y < 11.0, and contains Si of 1.0 mass% or less (excluding 0 mass%) in terms of SiO2.
[0019] In the ferrite sintered magnet of the embodiment of the present disclosure, the atomic ratio x (content of Ca) is 0.5 < x ≤ 0.65. When x is 0.5 or less or exceeds 0.65, a high residual magnetic flux density B r (hereinafter sometimes simply referred to as "B r ") and a high coercive force H cJ (hereinafter sometimes simply referred to as "coercive force" or "H cJ ") cannot be obtained.
[0020] The atomic ratio 1 - x (content of R) satisfies 0.35 ≤ 1 - x ≤ 0.5. That is, it satisfies the relationship x > 1 - x. R is at least one rare earth element and is an element essentially containing La. The content of rare earth elements other than La is preferably 50% or less of the total amount of R in molar ratio, and more preferably 0% (R = La, excluding impurities).
[0021] The atomic ratio y (content of Co) is 0.2 < Co < 0.35. When y is 0.2 or less or 0.35 or more, high H cJ cannot be obtained. Also, when y is 0.35 or more, the amount of Co used increases, and an increase in raw material cost is inevitable. It is more preferable that 0.27 ≤ Co ≤ 0.32. By setting it within a more preferable range, the magnet characteristics can be further improved.
[0022] The atomic ratio 2n - y (content of Fe) is 6.5 ≤ 2n - y < 11.0. When 2n - y is less than 6.5 or 11.0 or more, high B r and high H cJ cannot be obtained.
[0023] The above general formula is shown in terms of the atomic ratio of metal elements. For the composition containing oxygen (O), the general formula is: Ca x R 1-x Fe 2n-y Co y O α is represented. The number of moles α of oxygen is basically α = 19, but it varies depending on the valences of Fe and Co, the values of x, y, and n, etc. Also, due to the oxygen vacancies (vacancies) when fired in a reducing atmosphere, the change in the valence of Fe in the ferrite phase, the change in the valence of Co, etc., the ratio of oxygen to metal elements changes. Therefore, the actual number of moles α of oxygen may deviate from 19. For this reason, in the present invention, the composition is expressed in terms of the atomic ratio of metal elements that is most easily specified.
[0024] The main phase constituting the sintered ferrite magnet of the embodiment of the present disclosure is a compound phase (ferrite phase) having a hexagonal magnetoplumbite (M-type) structure. In general, magnetic materials, particularly sintered magnets, are composed of multiple compounds, and the compound that determines the characteristics (physical properties, magnetic properties, etc.) of the magnetic material is defined as the "main phase."
[0025] "Having a hexagonal magnetoplumbite (M-type) structure" means that when X-ray diffraction of a sintered ferrite magnet is measured under typical conditions, the X-ray diffraction pattern observed is primarily that of a hexagonal magnetoplumbite (M-type) structure.
[0026] As described below, in the manufacturing method of the sintered ferrite magnet according to the embodiment of the present disclosure, 1.0 mass% or less (excluding 0 mass%) of SiO2 is added as a sintering aid. The added SiO2 becomes a liquid phase component during firing (sintering) and exists as one component of the grain boundary phase in the sintered ferrite magnet. Therefore, the obtained sintered ferrite magnet contains 1.0 mass% or less (excluding 0 mass%) of Si in terms of SiO2.
[0027] At this time, by containing Si, the above general formula: Ca 1-x R x Fe 2n-y Co y will relatively decrease, but the ranges of x, y, n, etc. in the general formula will basically not change. The Si content is calculated by converting the compositions (mass%) of Ca, La, Fe, Co, and Si in the component analysis results of the sintered ferrite magnet (e.g., results from an ICP optical emission spectrometer) into the masses of CaCO3, La(OH)3, Fe2O3, Co3O4, and SiO2, and expressing the content ratio (mass%) relative to the total mass of 100.
[0028] An example of a method for producing the sintered ferrite magnet according to the embodiment of the present disclosure described above will be described below.
[0029] 2. Manufacturing method of sintered ferrite magnets The raw powder can be a compound such as oxide, carbonate, hydroxide, nitrate, or chloride of each metal, regardless of its valence. It may be a solution in which the raw powder is dissolved. Examples of Ca compounds include carbonate, oxide, and chloride of Ca. Examples of R compounds include oxides such as La2O3, hydroxides such as La(OH)3, and carbonates such as La2(CO3)3·8H2O. Examples of Fe compounds include iron oxide, iron hydroxide, iron chloride, and mill scale. Examples of Co compounds include oxides such as CoO and Co3O4, hydroxides such as CoOOH and Co(OH)2, carbonates such as CoCO3, and basic carbonates such as m2CoCO3·m3Co(OH)2·m4H2O (m2, m3, and m4 are positive numbers).
[0030] In order to promote the reaction during calcination, compounds containing B (boron), such as B2O3 and H3BO3, may be added up to about 1 mass% as necessary. The addition of H3BO3 is particularly effective in improving the magnetic properties. The amount of H3BO3 added is preferably 0.3 mass% or less, and most preferably about 0.1 mass%. H3BO3 also has the effect of controlling the shape and size of crystal grains during sintering, so it may be added after calcination (before pulverization or sintering) or both before and after calcination.
[0031] The raw material powders are mixed to satisfy the components and composition of the ferrite sintered magnet of the embodiment of the present disclosure described above, to obtain a mixed raw material powder. The blending and mixing of the raw material powders may be performed in either a wet or dry manner. The raw material powders can be mixed more uniformly by stirring with a medium such as steel balls. In the case of the wet method, it is preferable to use water as the dispersion medium. In order to increase the dispersibility of the raw material powder, a known dispersant such as ammonium polycarboxylate or calcium gluconate may be used. The mixed raw material slurry may be calcined as it is, or the raw material slurry may be dehydrated and then calcined.
[0032] The mixed raw material powder obtained by dry mixing or wet mixing is heated in an electric furnace, gas furnace, etc., to form a ferrite compound with a hexagonal magnetoplumbite (M-type) structure through a solid-phase reaction. This process is called "calcination," and the resulting compound is called a "calcined body." Therefore, the ferrite calcined body can be called a ferrite compound.
[0033] In the calcination step, a solid-phase reaction in which a ferrite phase is formed proceeds with an increase in temperature. If the calcination temperature is less than 1100°C, unreacted hematite (iron oxide) remains, resulting in poor magnetic properties. On the other hand, if the calcination temperature exceeds 1450°C, the crystal grains grow too much, and the pulverization step may require a long time. Therefore, the calcination temperature is preferably 1100°C to 1450°C. The calcination time is preferably 0.5 to 5 hours. The calcined body after calcination is preferably coarsely pulverized using a hammer mill or the like.
[0034] In the pulverization step, the calcined body is pulverized (finely pulverized) by a vibration mill, a jet mill, a ball mill, an attritor, or the like to obtain a powder of the calcined body (finely pulverized powder). The average particle size of the powder of the calcined body is preferably about 0.4 μm to 1.2 μm. When emphasis is placed on improving the magnetic properties, it is preferably about 0.4 μm to 0.7 μm, and more preferably 0.5 μm to 0.65 μm. When emphasis is placed on manufacturing costs (shortening the pulverization time, shortening the press cycle, etc.), it is preferably about 0.7 μm to 1.2 μm. In the embodiment of the present disclosure, the value measured by the air permeation method using a powder specific surface area measuring device (for example, SS-100 manufactured by Shimadzu Corporation) or the like is referred to as the average particle size (average grain size) of the powder. The pulverization step may be either dry pulverization or wet pulverization, or both may be combined. In the case of wet pulverization, water and / or a non-aqueous solvent (organic solvent such as acetone, ethanol, xylene, etc.) is used as a dispersion medium. Typically, a slurry containing water (dispersion medium) and the calcined body is produced. A known dispersant and / or surfactant may be added to the slurry in a solid content ratio of 0.2 mass% to 2 mass%. After wet pulverization, the slurry may be concentrated.
[0035] In the compacting step, the slurry after the pulverization step is press-molded in a magnetic field or without a magnetic field while removing the dispersion medium. By press-molding in a magnetic field, the crystal orientation of the powder particles can be aligned (oriented), and the magnetic properties can be improved dramatically. Furthermore, in order to improve the orientation, a dispersant and a lubricant may be added to the slurry before compaction at 0.1 mass% to 1 mass%, respectively. Furthermore, the slurry may be concentrated before compaction as necessary. Concentration is preferably performed by centrifugation, a filter press, or the like.
[0036] After the calcination step and before the molding step, 1.0 mass% or less (excluding 0 mass%) of SiO2 is added to 100 mass% of the calcined body or powder of the calcined body. The amount of SiO2 added is more preferably 0.55 mass% or more and 0.75 mass% or less. If the amount of SiO2 added is less than 0.55 mass%, the magnetic properties, especially the coercive force H cJ If it exceeds 0.75 mass%, the effect of improving the residual magnetic flux density B r The addition of SiO2 can be performed, for example, by adding SiO2 to the calcined body obtained by the calcination step and then carrying out the pulverization step, by adding SiO2 during the pulverization step, or by adding SiO2 to the powder of the calcined body after the pulverization step (finely pulverized powder), mixing them, and then carrying out the molding step.
[0037] In conventional SrLaCo magnets and CaLaCo magnets, it was common to add both SiO2 and CaCO3 (composite addition) as sintering aids, but in the manufacturing method of the sintered ferrite magnet of the embodiment of the present disclosure, only SiO2 is added as a sintering aid, and CaCO3 is not added. As shown in the examples, in the sintered ferrite magnet of the embodiment of the present disclosure, higher magnetic properties can be obtained by adding only SiO2 rather than by adding SiO2 and CaCO3 in combination. In addition to SiO2, Cr2O3, Al2O3, etc. may be added as a sintering aid. The amount of each of these added may be 1 mass% or less.
[0038] The compact obtained by press molding is degreased as necessary and then fired (sintered). Firing is carried out using an electric furnace, a gas furnace, or the like. Firing is preferably carried out in an atmosphere with an oxygen concentration of 10% by volume or more, more preferably 20% by volume or more, and most preferably 100% by volume. The firing temperature is preferably about 1150°C to 1250°C. The firing time is preferably 0 hours (no holding at the firing temperature) to about 2 hours.
[0039] In an embodiment of the present disclosure, the temperature is preferably increased and decreased during firing under the following conditions: the average rate of temperature increase in the temperature range from room temperature to 1100°C is less than 13.3°C / min (e.g., 5°C / min to 10°C / min), and the average rate of temperature increase in the temperature range from 1100°C to the firing temperature is 1°C / min or more and 10°C / min or less.
[0040] After the firing step, known manufacturing processes such as a machining step, a cleaning step, and an inspection step are performed, and finally, a sintered ferrite magnet is manufactured. EXAMPLES
[0041] The embodiments of the present disclosure will be described in more detail with reference to examples, but the embodiments of the present disclosure are not limited thereto.
[0042] Experimental Example 1 As an experimental example based on an embodiment of the present disclosure, the general formula Ca 1-x La x Fe 2n-y Co y CaCO3 powder, La(OH)3 powder, Fe2O3 powder, and Co3O4 powder were weighed out so that the atomic ratios were x, 1-x, 2n-y, and y shown in composition No. a-c in Table 1, and 0.1 mass% of H3BO3 powder was added to the total of 100 mass% of the weighed powders, and then the powders were mixed in a wet ball mill for 4 hours, dried, and sized to obtain three types of mixed raw material powders. The resulting mixed raw material powders were calcined in air at 1200°C for 3 hours, and three types of calcined bodies were obtained.
[0043] The calcined bodies thus obtained were coarsely pulverized in a small mill to obtain three types of coarsely pulverized powders of the calcined bodies. SiO2 shown in Samples No. 1 to 16 in Table 1 was added to 100 mass% of the coarsely pulverized powders of the calcined bodies thus obtained (samples No. 4, 10, and 16 were mixed with SiO2 and CaCO3 shown in Table 1 (addition amount converted to CaO)), and the mixture was finely pulverized in a wet ball mill using water as a dispersion medium until the average particle size shown in Table 1 was obtained (measured by air permeability method using a powder specific surface area measuring device (SS-100 manufactured by Shimadzu Corporation)), to obtain 16 types of finely pulverized slurries.
[0044] Each finely ground slurry obtained by the grinding process was molded at a pressure of approximately 2.4 MPa while applying a magnetic field of approximately 1 T using a parallel magnetic field molding machine (vertical magnetic field molding machine) in which the pressure direction and magnetic field direction are parallel, while removing the dispersion medium, to obtain 16 types of molded bodies.
[0045] The obtained compacts were each placed in a sintering furnace, and the temperature was increased from room temperature to 1100°C at an average rate of 6.67°C / min, then increased from 1100°C to 1220°C (firing temperature) at an average rate of 1°C / min, and sintered at 1220°C for 1 hour. After sintering, the temperature was decreased to room temperature at an average rate of 300°C / hr and cooled.
[0046] The B of the 16 types of sintered ferrite magnets obtained r , H cJ and H k / H cJ The measurement results are shown in Table 1. In Table 1, samples Nos. 4, 10, and 16 marked with an * next to the sample number are experimental examples (comparative examples) that do not satisfy the embodiments of the present disclosure, and the other samples not marked with an * are experimental examples based on the embodiments of the present disclosure. k / H cJ H in k is in the second quadrant of the J (magnetization magnitude)-H (magnetic field strength) curve, where J is 0.9×J r (J r is the remanent magnetization, J r =B r ) is the value of H at the position where
[0047] The atomic ratios in Table 1 indicate the atomic ratios (compositions) when the raw material powders were blended. The atomic ratios (composition of the sintered magnet) in the sintered body (sintered ferrite magnet) after firing can be calculated based on the atomic ratios when blended, taking into account, for example, the amount of additives (H3BO3, etc.) added before the calcination step and the amount of SiO2, etc. added after the calcination step and before the shaping step, and the calculated values are basically the same as the results of analyzing the sintered ferrite magnet with an ICP optical emission spectrometer (for example, Shimadzu ICPV-1017).
[0048] [Table 1]
[0049] As shown in Table 1, the sintered ferrite magnets that are experimental examples based on the embodiments of the present disclosure have a high residual magnetic flux density B r and high coercive force H cJ (Samples No. 5 to 9 and Samples No. 11 to 15) or have a high residual magnetic flux density B equal to or higher than that of conventional CaLaCo magnets. r and high coercive force H cJ In addition, the amount of Co used can be reduced (samples Nos. 1 to 3, Co = 0.27) compared to conventional CaLaCo magnets (containing Co at an atomic ratio of about 0.3).
[0050] Furthermore, when the samples have the same compounded composition, the ferrite sintered magnets that are examples based on the embodiments of the present disclosure have higher magnetic properties than experimental examples (comparison examples) that do not satisfy the embodiments of the present disclosure, in which SiO2 and CaCO3 are added in combination (compare Nos. 1 to 3 with Sample No. 4, Sample Nos. 5 to 9 with Sample No. 10, and Sample Nos. 11 to 15 with Sample No. 16). In other words, the addition of only SiO2 results in higher magnetic properties than the combined addition of SiO2 and CaCO3.
[0051] Furthermore, when comparing samples with the same composition but different average particle sizes of the pulverized powder (No. 3 and Sample No. 4, Sample No. 9 and Sample No. 10, Sample No. 15 and Sample No. 16), the ferrite sintered magnet, which is an example based on the embodiment of the present disclosure, has magnetic properties (especially coercive force H cJ ) equal to or better than those of experimental examples (comparative examples) that do not satisfy the embodiment of the present disclosure, despite having a larger average particle size. That is, the ferrite sintered magnet, which is an experimental example based on the embodiment of the present disclosure, has the characteristic that its magnetic properties are less likely to deteriorate even when the average particle size is increased. The ability to increase the average particle size can shorten the pulverization time and the dehydration time and press cycle during press molding in the molding process, and the effect of reducing process costs can be expected. Also, when the press cycle is shortened, the mold life during press molding becomes longer, and the effect of reducing manufacturing costs can be expected.
[0052] The ferrite sintered magnet of the embodiment of the present disclosure satisfies x > 1 - x (Ca > R (in this experimental example, Ca > La)). In contrast, conventional CaLaCo magnets basically have Ca = La or Ca < La (see Patent Document 3, etc.). The atomic weight of Ca is 40.078, and the atomic weight of La is 138.905 (the atomic weights of R other than La are equal to or greater than that of La). Therefore, the ferrite sintered magnet (Ca > La) of the embodiment of the present disclosure has a lower content of La with a larger atomic weight and a higher content of Ca with a smaller atomic weight than the conventional CaLaCo magnet (Ca ≤ La), so the density (g / cm 3 ) of the sintered magnet (sintered body) is lower than that of the conventional CaLaCo magnet. For example, the sintered body density when Ca = 0.5 and La = 0.5 is about 5.09 g / cm 3 , and the sintered body density when Ca = 0.55 and La = 0.45 is 5.06 g / cm 3 , and although it is slightly lower, the density is lower when Ca > La.
[0053] In other words, if the magnet dimensions are the same, the sintered ferrite magnet of the embodiment of the present disclosure will be lighter in weight than a conventional CaLaCo magnet. For example, if a sintered ferrite magnet of the embodiment of the present disclosure and a conventional CaLaCo magnet of the same dimensions are used in an EV motor, the motor using the sintered ferrite magnet of the embodiment of the present disclosure will be lighter in weight. However, as mentioned above, the magnetic properties are equal to or better than those of the conventional CaLaCo magnet. Therefore, by using the sintered ferrite magnet of the embodiment of the present disclosure, it is expected that the weight of the motor can be reduced without degrading the performance. [Industrial Applicability]
[0054] High residual magnetic flux density B exceeding that of conventional CaLaCo magnets r and high coercive force H cJ or a high residual magnetic flux density B equal to or greater than that of conventional CaLaCo magnets. r and high coercive force H cJ The sintered ferrite magnet according to the embodiment of the present disclosure has the above properties and can reduce the amount of Co used compared to conventional CaLaCo magnets, and can be suitably used in various motors, etc.
Claims
1. A general formula showing the atomic ratio of the metal elements Ca, R, Fe and Co (wherein R is at least one rare earth element and essentially contains La): Ca x R 1-x Fe 2n-y Co y In the formula, x, y, and n (wherein 2n is a molar ratio expressed as 2n=(Fe+Co) / (Ca+R)) are 0.5<x≦0.65, 0.2<y<0.35, 6.5≦2ny<11.0, and SiO 2 A sintered ferrite magnet containing 1.0 mass% or less (excluding 0 mass%) of Si.
2. SiO 2 2. The sintered ferrite magnet according to claim 1, containing 0.55 mass % or more and 0.75 mass % or less of Si, calculated as a percent by mass.
3. 3. The sintered ferrite magnet according to claim 1, wherein 0.27≦y≦0.
32.
4. A general formula showing the atomic ratio of the metal elements Ca, R, Fe and Co (wherein R is at least one rare earth element and essentially contains La): Ca x R 1-x Fe 2n-y Co y In the formula, x, y, and n (wherein 2n is a molar ratio expressed as 2n=(Fe+Co) / (Ca+R)) are 0.5<x≦0.65, 0.2<y<0.35, 6.5≦2ny<11.0, A raw material powder mixing process for mixing raw material powders satisfying the above to obtain a mixed raw material powder; a calcination step of calcining the mixed raw material powder to obtain a calcined body; A grinding step of grinding the calcined body to obtain a powder of the calcined body; A molding step of molding the powder of the calcined body to obtain a molded body; a sintering step of sintering the molded body to obtain a sintered body; Including, After the calcination step and before the molding step, 1.0 mass% or less (excluding 0 mass%) of SiO 2 A method for producing a sintered ferrite magnet comprising adding
5. After the calcination step and before the molding step, SiO is added in an amount of 0.55 mass% or more and 0.75 mass% or less with respect to 100 mass% of the calcined body or the powder of the calcined body. 2 The method for producing a sintered ferrite magnet according to claim 4, further comprising the step of adding
6. 6. The sintered ferrite magnet according to claim 4 or 5, wherein 0.27≦y≦0.
32.
7. The method for producing a sintered ferrite magnet according to claim 4, wherein in the sintering step, the average heating rate in the temperature range from room temperature to 1100°C is less than 13.3°C / min, and the average heating rate in the temperature range from 1100°C to the sintering temperature is 1°C / min or more and 10°C / min or less.
8. After the calcination step, CaCO 3 The method for producing a sintered ferrite magnet according to claim 4, wherein no additive is added.
Citation Information
Patent Citations
Ferrite magnet and its manufacturing method
JP1998149910A
Sintered magnet and motor
JP1999154604A
Oxide magnetic material and sintered magnet
JP2006104050A